Evaluating the Implementation of Kurikulum Merdeka in Senior High School English Classes Using the CIPP Model - Eva Meidi Kulsum; Riyadh Ahsanul Arifin; Windriani Lutfiah Azzahra (UIN Sunan Gunung Djati Bandung, 2026)
This study evaluates the implementation of Kurikulum Merdeka in English language teaching at senior high schools in Kabupaten Bandung, using the CIPP (Context, Input, Process, Product) evaluation model. A mixed-methods design was applied, involving 131 participants from four schools, including principals, vice principals, teachers, and students. Data were collected through questionnaires, observations, and interviews, with instruments tested for validity and reliability. Findings show encouraging progress alongside key challenges. In context, schools (93.33%) and teachers (85.83%) affirmed strong alignment with institutional vision and policy, while students (72.93%) found lessons more engaging and relevant. Input results indicated sufficient training and facilities (80–85%), though students rated this lower (73.49%). The process dimension reflected strong implementation by schools (85%) and teachers (88.12%) through differentiation, project-based learning, and feedback, but student engagement was weaker (71.20%). In terms of product, schools (80%) and teachers (80.83%) observed improved performance, yet only 58.79% of students felt personal progress. Overall, the curriculum shows contextual relevance, resource readiness, and positive outcomes, but student experiences vary. Challenges include inconsistent transfer of teacher training to practice, supervision that often feels administrative, and student concerns over workload and confidence. Strengthening teacher capacity, fostering meaningful supervision, and building learner confidence are crucial to ensuring that Kurikulum Merdeka not only aligns with policy but also delivers deeper benefits to students.